"Una publicación de artista es una tecnología multitudinaria”: collaboration exercises between humans and machines (Anclajes, 2025)
Digital literature seeks to destabilize the figure of the author through collective creations, non-creative writing and automated textual productions, among other procedures. Beyond all the possibilities of co-authorship that technopoetics promote, this article analyzes, from a posthumanist perspective, a series of literary bots programmed by the collectives Broken English and Aceleraditxs as collaborations between humans and machines. Just as the concept of the Anthropocene weakens the distinction between the natural and the artificial, that is, between nature and culture, from a posthumanist perspective the world can be approached in terms of “networks” in which the human loses unity and privilege as an agent.
Keywords: Aceleraditxs; Broken English; Literary criticism; poetry; 21st Century